2004
DOI: 10.1016/s1054-139x(03)00278-7
|View full text |Cite
|
Sign up to set email alerts
|

Caught in the Crossfire: the effects of a peer-based intervention program for violently injured youth

Abstract: A peer-based program that intervenes immediately after, or very soon after, youth are violently injured can directly reduce at-risk youth involvement in the criminal justice system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 0 publications
2
54
0
2
Order By: Relevance
“…Research has shown that these programs have significant benefits, including sustained reductions in perpetration and victimization of peer violence ( 9 ). Evaluation of a specific program found that participants were 70% less likely than nonparticipating youths to be arrested for any offense during the 6 months after the program ( 10 ). …”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that these programs have significant benefits, including sustained reductions in perpetration and victimization of peer violence ( 9 ). Evaluation of a specific program found that participants were 70% less likely than nonparticipating youths to be arrested for any offense during the 6 months after the program ( 10 ). …”
Section: Discussionmentioning
confidence: 99%
“…This study also highlights a need for the inclusion of case management, which involves connecting youth to resources in the community, as a key component of a hospital‐based youth violence intervention. The importance of case management for youth affected by violence has been found in other programs reported in the literature 25–28 . We published a systematic review of ED‐based youth violence secondary prevention programs 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the cross-sectoral approach to implementing prevention programmes has proved to be successful, consideration of all stakeholders' positions is important to facilitate success. Becker, Hall, Ursic, Jain, and Calhoun (2004) acknowledged the need for multi-disciplinary violence prevention programmes, but suggested that there is a place for targeted specific intervention programmes. The Caught in the Crossfire programme implemented in Oakland, California, is a peerbased violence prevention intervention programme for youth who have been hospitalised for violent injuries (Becker et al, 2004).…”
Section: Community-based Approaches To Violence Preventionmentioning
confidence: 99%